2022
DOI: 10.3389/fsufs.2022.836299
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Dietary Recommendations Achievement From Latin American College Students During the COVID-19 Pandemic Lockdown

Abstract: This study aimed to compare the diet quality of different dietary patterns among college students from Latin American countries, including vegetarians, vegans, and omnivores during the COVID-19 pandemic. A cross-sectional, observational, multicenter study was conducted including a non- probabilistic sample of university students from 10 countries. University students were invited to participate in the study through social network platforms. Participants were self-reported to have followed a specific dietary pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 89 publications
0
0
0
Order By: Relevance
“…By relating the sex variable, we found that women had greater changes in their diet by 90.49% compared to authors such as Murillo et al ( 20 ) and Miller et al ( 27 ), who mention not finding a significant relationship. In contrast, Ferrara et al ( 28 ) mention that being a woman was a predictor (OR:2.7) of a greater risk of unhealthy eating behaviors, both before and after the pandemic; and being older during the pandemic.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…By relating the sex variable, we found that women had greater changes in their diet by 90.49% compared to authors such as Murillo et al ( 20 ) and Miller et al ( 27 ), who mention not finding a significant relationship. In contrast, Ferrara et al ( 28 ) mention that being a woman was a predictor (OR:2.7) of a greater risk of unhealthy eating behaviors, both before and after the pandemic; and being older during the pandemic.…”
Section: Discussioncontrasting
confidence: 51%
“…This agrees with Villaseñor et al ( 19 ), who reported that during COVID-19 confinement, there was an increase in the consumption of unhealthy foods among Mexicans. The study by Murillo et al ( 20 ), which included students from 10 countries, found a greater probability of following a prudent eating pattern when living in Mexico (OR:1.57) and Peru (OR:1.65).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted in Latin America, which included university students, showed that individuals following a plant-based diet had the highest consumption of legumes compared to other students following other diets such as western, prudent, etc. [28].…”
Section: Discussionmentioning
confidence: 99%